Association of urinary heavy metals co-exposure and adult depression: Modification of physical activity - Fu, Xihang; Li, Huiru; Song, Lingling; Cen, Manqiu; Wu, Jing (Neurotoxicology (Park Forest South), 2023)
This study aimed to evaluate the association between urinary heavy metal mixture exposure and depression, and the modifying role of physical activity in the effects of heavy metal mixture on depression risk was also considered. Data of this study were derived from the National Health and Nutrition Examination Survey 2011–2016. Depression was measured by the Patient Health Questionnaire. We first selected 6 (cadmium, cobalt, tin, antimony, thallium, and mercury) from 14 heavy metals through elastic net regression for further analysis. Then binomial logistic regression, generalized additive model, environment risk score (ERS), and weighted quantile sum (WQS) regression were adopted to assess the effects of six metals individual and cumulative exposure on depression risk. Finally, we also examined whether physical activity could mitigate the effects of heavy metal co-exposure on depression risk. Totally, 4212 participants were included and 7.40% of subjects were with depression. We found urinary tin and antimony were separately associated with increased odds of depression (Sb: OR = 1.285, 95% CI: 1.064–1.553; Sn: OR = 1.281, 95% CI: 1.097–1.495), and a linear dose-response relationship between tin and depression was also noticed (P < 0.05). Meanwhile, urinary heavy metals co-exposure was positively related to depression risk (ERSQ4: OR = 2.691, 95% CI: 1.399–5.174; WQSpositive: OR = 1.465, 95% CI: 1.063–2.021), in which tin, antimony, and cadmium were identified with greater contributions to the overall mixture effect. In both ERS and WQS models, the significant positive association between the metal mixture and depression risk remained only in those who were inactive in physical activity. Our study concluded the detrimental effect of heavy metals in combined exposure on the risk of depression, which might be attenuated by physical activity. •Urinary tin and antimony were separately associated with elevated depression risk.•Heavy metals co-exposure was significantly associated with depression risk.•Tin and antimony were identified with most contribution to overall mixture effect.•Physical activity might counteract the overall detrimental effects of heavy metals.